ChemInform Abstract: The N‐Silylation of Sulfoximines. Issue 10 (February 2016) - Peng, Haibo; Yu, Jin‐Tao; Bao, Weijie; Xu, Jinwei; Cheng, Jiang
Abstract: A simple procedure is elaborated for the copper‐catalyzed N‐silylation of sulfoximines (I) and (IV) in wet acetonitrile using di(tert‐butyl) peroxide as an oxidant.